ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP BERBANTUAN SOAL ONTEKSTUAL PADA MATERI BANGUN RUANG SISI DATAR - Kurniawan, Apri; Setiawan, Diki (IKIP Siliwangi, 2019)
Mathematical problem solving abilities will influence student learning achievement is the background of this study. While, the aim is to describe the mathematical problem solving abilities of Junior High School students in the matter polyhedron in the form contextual questions with indicators of student’s abilities to solve problem. Qualitative descriptive is the tipe of this study with a sample of VIII E SMP Negeri 2 Sampang in Cilacap district. Data obtained through tes techniques using instruments that have been validated and then given a score so that the percentage of each indicator is collected and the average process is performed. The instrument used consists of 5 question with each question consisting of 4 indicators of abilitiy. Research data shows 67 % of the students are able to understand the problem, 71% of students can plan completion, 49 % of students can run a completion plan, 42 % of students check back. The data show that the mathematical problem solving abilities of Junior High School students are still relatively medium, so an effort is needed to improve.